Three new species and one new subspecies of Deserticossus Yakovlev, 2006 (Lepidoptera: Cossidae) from Kazakhstan, Kyrgyzstan and Russia, with world catalogue of the genus - Yakovlev, Roman V.; Witt, Thomas J. (Zootaxa, 2017)
Three new species and one new subspecies of the genus Deserticossus Yakovlev, 2006 are described: Deserticossus doroshkini Yakovlev & Witt sp. nov. from eastern Kazakhstan (Tarbagatai Mts.), D. selevini Yakovlev & Witt sp. nov. from southeastern Kazakhstan (Malye Boguty Mts.), D. kamelini Yakovlev & Witt sp. nov. from Kyrgyzstan (Fergana Valley), and D. tsingtauana didenkoi Yakovlev & Witt subsp. nov. from Russia (Southern Siberia, Buryatia Republic). The described species and subspecies of Deserticossus are listed, with notes on the type material, synonymies, and distribution for each taxon.